Interpretation of ecotoxicity tests using Enchytraeus albidus: Weight of soil characteristics in conditions of diffuse pollution - Andrea Chacon-Hurtado; Juliette Faburé; Laura Sereni; Sylvie Nélieu; Nathalie Cheviron; Ghislaine Delarue; Emmanuelle Baudry; Isabelle Lamy (Ecotoxicology and Environmental Safety)
One way to evaluate the impact of chemical substances released in the ecosystems is the use of terrestrial organisms in ecotoxicological bioassays. Enchytraeus albidus (Oligochaeta) is a species commonly used in such standardized bioassays aiming at identifying biological responses as life traits (survival and reproduction) using artificial spiked soils or in situ contaminated soils. However, in the latter case, it is known that other factors such as soil characteristics may affect the responses in E. albidus. We hypothesized that, in cases of low diffuse pollution, soil characteristics are major confounding factors that interfere with the interpretation of life trait responses in bioassays when their influence outweighs that of the diffuse pollution itself. To evaluate these confounding factors, 20 soils were collected from a low-contamination area encompassing diverse landscapes (urban, peri-urban, and rural) that exhibited gradients in pedological characteristics, biological parameters, and organic and inorganic contaminant levels, all within the range of classical values considered optimal for reproduction. E. albidus individuals were exposed to each soil sample, and survival and reproduction were monitored as life traits. Soil clustering and multifactorial analysis were employed to identify the confounding factors. Regardless of the life trait, low and sublethal contamination was rarely an explanatory factor for the responses of E. albidus. Survival was unaffected by soil characteristics or diffuse pollution. In contrast, reproduction was significantly and positively associated with soil pH and the levels of exchangeable sodium, calcium carbonate, molybdenum, PAHs, and insecticides, while it was negatively influenced by aluminum and exchangeable manganese. These findings suggest that studies conducted under conditions of diffuse, sublethal contamination should consider multiple natural soil characteristics in ecotoxicological bioassays to enable meaningful comparisons.